The Consciousness of Pain in The Black Heralds - Merino, Antonio (2019)
With The Black Heralds (1919), Vallejo begins his first literary archeology that already hoarded, from previous compositions, a broad knowledge of the symbolic structures of the literary currents that flooded the gatherings and academic forums of the early twentieth century. So much so that a poem like «Campanas muertas» («Dead Bells»), published in La Reforma on november 13, 1915, that is, several years before the publication of The Black Heralds, will have a major importance. In addition, in that same year of 1915, Vallejo draws a new line in its complex poetic universe, benefiting from new friends and «fellow travelers» (Orrego, Garrido, Imaña, Haya de la Torre, etc.) and readings of Schiller, Poe and Tennyson that, with the years, will allow him to know better his reality and his time; a time that, in Vallejo, is always dialectical, that is, contradictory, pessimistic, of exaltation, of memories and expectations, but always human.